Paediatric anaemia in rural Kenya and the role of travel time to emergency care services - Musau, Moses M.; Khazenzi, Cynthia; Akech, Samuel; Omondi, Evans; Okiro, Emelda A.; Snow, Robert W.; Macharia, Peter M.; Kamau, Alice (Frontiers in Epidemiology, 2025)
BackgroundAccess to emergency care (EC) services is crucial for severe anaemia outcome. Limited information exists on the association between travel times to EC services and the presentation and severity of anaemia upon hospital admission. Here, we investigate the association between travel time and presentation of severe anaemia (compared to mild/moderate anaemia) at admission in western Kenya.MethodsData from January 2020 to July 2023 from Busia County Referral Hospital were assembled for paediatric admissions aged 1–59 months residing in Busia County. Travel time from a patient's village to the hospital was calculated using a least cost path algorithm. Anaemia severity was categorised as mild (Hb ≥ 7–<10 g dl−1), moderate (Hb ≥ 5–<7 g dl−1) and severe (Hb < 5 g dl−1). We fitted a geostatistical model accounting for covariates to estimate the association between travel times to EC services and severe anaemia presentation.ResultsSevere anaemia admissions had the highest median travel time of 36 min (IQR: 25,54) (p-value: <0.001). Compared to children living within a 30 min travel time to the hospital, the adjusted odds ratio (AOR) of severe anaemia presentation relative to mild/moderate anaemia was 2.44 (95% CI: 1.63–3.55) for those residing within 30-59 min. For travel times of 60–89 min, the AOR was 3.55 (95% CI: 1.86–6.10) and for ≥90 min, the AOR was 3.41 (95% CI: 1.49–7.67).ConclusionTravel time is significantly associated with the severity of paediatric anaemia presentations at hospitals. Addressing disparities in travel times such as strategic bolstering of lower-level facilities to offer EC services, is crucial for implementing new interventions and optimizing existing hospital-linked interventions to enhance healthcare delivery.